Induction of apoptosis and autophagy via sirtuin1- and PI3K/Akt/mTOR-mediated pathways by plumbagin in human prostate cancer cells - Zhou ZW; Li XX; He ZX; Pan ST; Yang Y; Zhang X; Chow K; Yang T; Qiu JX; Zhou Q; Tan J; Wang D; et al. (Dove Medical Press, 2015)
Zhi-Wei Zhou,1,2 Xing-Xiao Li,1 Zhi-Xu He,2 Shu-Ting Pan,1,3 Yinxue Yang,4 Xueji Zhang,5 Kevin Chow,1 Tianxin Yang,6 Jia-Xuan Qiu,3 Qingyu Zhou,1 Jun Tan,7 Dong Wang,8 Shu-Feng Zhou1,2 1Department of Pharmaceutical Sciences, College of Pharmacy, University of South Florida, Tampa, FL, USA; 2Guizhou Provincial Key Laboratory for Regenerative Medicine, Stem Cell and Tissue Engineering Research Center and Sino–US Joint Laboratory for Medical Sciences, Guizhou Medical University, Guiyang, Guizhou, People’s Republic of China; 3Department of Oral and Maxillofacial Surgery, The First Affiliated Hospital of Nanchang University, Nanchang, Jiangxi, People’s Republic of China; 4Department of Colorectal Surgery, General Hospital of Ningxia Medical University, Yinchuan City, Ningxia, People’s Republic of China; 5Research Center for Bioengineering and Sensing Technology, University of Science and Technology Beijing, Beijing, People’s Republic of China; 6Department of Internal Medicine, University of Utah and Salt Lake Veterans Affairs Medical Center, Salt Lake City, UT, USA; 7Department of Psychiatry and Behavioral Neurosciences, Silver Child Development Center, Rashid Laboratory for Developmental Neurobiology, Morsani College of Medicine, University of South Florida, Tampa, FL, USA; 8Cancer Center, Daping Hospital and Research Institute of Surgery, Third Military Medical University, Chongqing, People’s Republic of China Abstract: Plumbagin (PLB) has been shown to have anticancer activities in animal models, but the role of PLB in prostate cancer treatment is unclear. This study aimed to investigate the effects of PLB on apoptosis and autophagy and the underlying mechanisms in human prostate cancer cell lines PC-3 and DU145. Our study has shown that PLB had potent pro-apoptotic and pro-autophagic effects on PC-3 and DU145 cells. PLB induced mitochondria-mediated apoptosis and autophagy in concentration- and time-dependent manners in both PC-3 and DU145 cells. PLB induced inhibition of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt)/mammalian target of rapamycin (mTOR) and p38 mitogen-activated protein kinase (MAPK) pathways and activation of 5'-AMP-dependent kinase (AMPK) as indicated by their altered phosphorylation, contributing to the pro-autophagic activity of PLB. Modulation of autophagy altered basal and PLB-induced apoptosis in both cell lines. Furthermore, PLB downregulated sirtuin 1 (Sirt1), and inhibition of Sirt1 enhanced autophagy, whereas the induction of Sirt1 abolished PLB-induced autophagy in PC-3 and DU145 cells. In addition, PLB downregulated pre-B cell colony-enhancing factor/visfatin, and the inhibition of pre-B cell colony-enhancing factor/visfatin significantly enhanced basal and PLB-induced apoptosis and autophagy in both cell lines. Moreover, reduction of intracellular reactive oxygen species (ROS) level attenuated the apoptosis- and autophagy-inducing effects of PLB on both PC-3 and DU145 cells. These findings indicate that PLB promotes apoptosis and autophagy in prostate cancer cells via Sirt1- and PI3K/Akt/mTOR-mediated pathways with contribution from AMPK-, p38 MAPK-, visfatin-, and ROS-associated pathways. Keywords: AMPK, visfatin, PC-3, DU145, ROS